Performance study on effect of convolutional coding in WCDMA system with AWGN and multipath rayleigh fading channel: article / Siti Noorafiza Sudin - Sudin, Siti Noorafiza (2010)
This Thesis highlights the performance of Convolutional coding in WCDMA with different channel. The main objective of this thesis is to investigate the effect of Convolutional coding with different channel condition such as AWGN and multipath Rayleigh fading channel with different Doppler shift in WCDMA system. A Convolutional code is used to correct and detect any error that is occurs in this communication system. The modulation technique that is used in this thesis is QPSK. The system model was constructed and simulated using MATLAB software version 6.5. From the result obtained, the system with Convolutional coding much better in term of BER compared to the system without channel coding for both type of fading.